Personal occupational exposure to total welding fume - Seleme, Dave Pooke (My University, 2016)
Background: The primary route of occupational exposure to total welding fume is through inhalation. Recurrent and prolonged inhalation via occupational exposure to total welding fume at concentrations above the 5 mg/m3 is likely to cause pulmonary and respiratory diseases, such as metal fume fever, chronic bronchitis, occupational asthma, manganese poisoning and arc welder’s siderosis. The severity of the personal occupational exposure to total fume is determined by a number of factors which entail the composition of the welding electrode, welding base, the type of welding, the surface coating of the welding base, welder’s positioning and the effectiveness of existing control measures. Aim and Objectives: This study aimed to determine if employees were overexposed to total welding fumes during Manual Metal Arc (MMA) welding operations in a workshop environment of a large coal-fired power generating utility from August to September 2011, in the Free State province of SA. The specific objectives for this study were: · To describe personal occupational exposure to total welding fume; · To compare personal occupational exposure to total welding fume to the Occupational Exposure Limit (OEL) of 5 mg/m3. · To identify the most exposed occupations Methodology: This employed a descriptive cross-sectional study design. This study was conducted in a workshop in the Free State province of South Africa (SA), during MMA welding operations spanning August to September 2011. The personal dust samples of total welding fume were collected in strict accordance with Part 1 of International Standards Organization (ISO) 10882 of 2001 and were compared to the SA OEL of 5 mg/m3. The personal dust samples of total welding fume were collected by a sampling train which consisted of constant battery operated sampling pump, flexible tubing, open-face cassette, 37 mm mixed cellulose acetate filter. The assembled and calibrated sampling trains were positioned inside the welding helmets of the employees within the breathing zone during data collection. Data was analysed by means of gravimetric weighing followed by determination of personal occupational exposure concentrations by standard calculations. Results: Fifty samples of personal occupational exposure to total welding fume were collected. Two samples exceeded the occupational exposure limit of 5 mg/m3. The sum of the personal occupational exposure concentrations to total welding fume was 95.91 mg/m3. The arithmetic mean was 1.918 mg/m3 and median 1.595 mg/m3. The highest (maximum) measured personal occupational exposure concentration was 7.12 mg/m3 whilst the lowest (minimum) was 0.46 mg/m3. The geometric mean was 1.631 mg/m3, geometric standard deviation 1.742 mg/m3 while the standard deviation was 1.278 mg/m3. The percentage exceedance of the occupational exposure limit was 4%. Conclusion: This study indicated that students were the most exposed employees followed by welders, utility personnel and boilermakers. This was due to students performing extensive welding, and the resultant incorrect students positioning during welding. Recommendations: Existing engineering control measures, which included blower fans and local extraction ventilation system (LEV) must be sustained and maintained in good working order in order to reduce personal occupational exposure to total welding fume. Furthermore a mobile local extraction ventilation system must be provided. The issued disposable particulate mask with a protection factor of FFP2 must be substituted with a ventilated disposable particulate mask with the same protection factor (FFP2) but that is lined up with activated carbon layer. The disposable particulate mask with a protection factor of FFP2 means that it will offer inhalation protection against the total welding fume exposure concentrations up to 10 times the occupational exposure limit if properly used as opposed to FFP1 which offers inhalation protection up to 5 times the occupational exposure limit. The disposable particulate mask with a protection factor of FFP3 offers a better protection than the one with FFP1 and FFP2 as it protects up to 20 times the occupational exposure limit. The proper usage, care and maintenance of the disposable particulate mask are important elements in achieving the maximum inhalation protection. The activated carbon layer will assist in the capturing of the gaseous components of the welding pollutants which will prevent the inhalation of such gaseous components by exposed employees.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Public Health (Occupational Hygiene).